How Much Does Bad Hay Cost a Beef Cattle Producer? - Matthew J. Hersom; Todd A. Thrift (EDIS, 2018)
Everyone likes a good bargain, but when it comes to hay, low price often equates to low nutritional value. Because hay is often sold on a large round-bale basis, savings from the good bargain can decrease substantially if there is a negative impact on the cow herd nutritional program. This 4-page fact sheet discusses intake limitations, energy limitations, protein limitations, examples of hay quality, and bad hay’s impact on cow body condition. Written by Matt Hersom and Todd Thrift, and published by the UF/IFAS Department of Animal Sciences, February 2018. http://edis.ifas.ufl.edu/an339